AN OPEN RANDOMIZED STUDY COMPARING DISULFIRAM AND ACAMPROSATE IN THE TREATMENT OF ALCOHOL DEPENDENCE - Avinash De Sousa; Alan De Sousa (2005)
To compare the efficacy of acamprosate (ACP) and disulfiram (DSF) for preventing alcoholic relapse in routine clinical practice.One hundred alcoholic men with family members who would encourage medication compliance and accompany them for follow-up were randomly allocated to 8 months of treatment with DSF or ACP. Weekly group psychotherapy was also available. The psychiatrist, patient, and family member were aware of the treatment prescribed. Alcohol consumption, craving, and adverse events were recorded weekly for 3 months and then fortnightly. Serum gamma glutamyl transferase was measured at the start and the end of the study.At the end of the trial, 93 patients were still in contact. Relapse (the consumption of >5 drinks/40 g of alcohol) occurred at a mean of 123 days with DSF compared to 71 days with ACP (P = 0.0001). Eighty-eight per cent of patients on DSF remained abstinent compared to 46% with ACP (P = 0.0002). However, patients allocated to ACP had lower craving than those on DSF (P = 0.002).DSF is superior to ACP for preventing relapse in alcohol-dependent men with good family support. Further comparisons between these two drugs in different treatment settings and populations are warranted.